2009
DOI: 10.1108/14684520910969907
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing satisfaction and loyalty in online shopping: an integrated model

Abstract: Purpose -Taking into consideration external (technology acceptance factors, website service quality) as well as internal (specific holdup cost) factors, this paper aims to explore how internet customer satisfaction and loyalty can be associated with each other and how they are affected by these dynamics. Design/methodology/approach -This study adopts structural equation modelling (SEM) as the main analytical tool. It investigates the shopping experiences of users of the major shopping websites of Taiwan. Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
141
1
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(194 citation statements)
references
References 38 publications
(53 reference statements)
20
141
1
21
Order By: Relevance
“…Srinivasan, Anderson, and Ponnavolu (2002b) also reported that interactivity influenced customer e-loyalty (Balabanis, Reynolds, & Simintiras, 2006). Despite customer interface quality, Oliveira (2007) also found that e-SERVQUAL directly linked to customer e-loyalty (Lin & Sun, 2009). This is due to the fact that acquiring new customers is costly exercise and the existing customer purchase more (Long & McMellon, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Srinivasan, Anderson, and Ponnavolu (2002b) also reported that interactivity influenced customer e-loyalty (Balabanis, Reynolds, & Simintiras, 2006). Despite customer interface quality, Oliveira (2007) also found that e-SERVQUAL directly linked to customer e-loyalty (Lin & Sun, 2009). This is due to the fact that acquiring new customers is costly exercise and the existing customer purchase more (Long & McMellon, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…TAM theory is based on this idea: Perceived Usefulness (PU) and Perceived Easiness of Use (PEOU) determine how users act towards technology and the extent of its use. The online purchaser's decisions are directly linked with his degree of acceptance of technology (Shih, 2004), making online shopping easier to increase customer's satisfaction and, consequently, his long term loyalty (Lin & Sun, 2009). …”
Section: Website Technological Level and E-service Qualitymentioning
confidence: 99%
“…The research (Lin & Sun, 2009) shows how TAM is useful and underlines that it influences, in a determining way, customer attitude and the inclination to re-purchase.…”
Section: Website Technological Level and E-service Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies exploring the online customer experience have overlooked the variable of the length of time spent on the website. Limited research from Ludin and Cheng (2014) and Luo et al (2010) acknowledge that the length of time spent searching online may be influenced by the quality of the information provided. The findings highlight that the website characteristics (including: website aesthetics, level of control, information quality, website credibility and flow) influence how long customers are willing to spend on the website, poor website characteristics result in customers spending longer searching on the website, proving hypothesis H2.…”
Section: Theoretical Contributionsmentioning
confidence: 99%